Retracted: Pulmonary functions in pregnancy complicated with anemia - Dash, Subhalaxmi; Nanda, Sudhanshu Sekhara; Behera, Ashok Kumar (International Journal of Research in Medical Sciences, 2017)
The article titled, "Pulmonary functions in pregnancy complicated with anemia", published in the International Journal of Research in Medical Sciences, Volume 2, Issue 4, 2014, Pages 1431-1437, DOI: 10.5455/2320-6012.ijrms20141135 is being retracted. It has been observed that the article contains several overlapping text sections from a previous published article titled, "Dynamic lung functions in pregnancy complicated with anemia" published in the printed version of Orissa Medical Journal, Volume 34 Issue 1, 2014, pages 103-110.